The GALAH survey: temporal chemical enrichment of the galactic disc. Issue 2 (12th November 2019) - Lin, Jane; Asplund, Martin; Ting, Yuan-Sen; Casagrande, Luca; Buder, Sven; Bland-Hawthorn, Joss; Casey, Andrew R; De Silva, Gayandhi M; D'Orazi, Valentina; Freeman, Ken C; Kos, Janez; Lind, K; et al.
ABSTRACT: We present isochrone ages and initial bulk metallicities ($\rm [Fe/H]_{bulk}$, by accounting for diffusion) of 163 722 stars from the GALAH Data Release 2, mainly composed of main-sequence turn-off stars and subgiants ($7000\, K> T_{ eff}> 4000\, K$ and $\log g>3$ dex). The local age–metallicity relationship (AMR) is nearly flat but with significant scatter at all ages; the scatter is even higher when considering the observed surface abundances. After correcting for selection effects, the AMR appears to have intrinsic structures indicative of two star formation events, which we speculate are connected to the thin and thick discs in the solar neighbourhood. We also present abundance ratio trends for 16 elements as a function of age, across different $\rm [Fe/H]_{bulk}$ bins. In general, we find the trends in terms of [X/Fe] versus age from our far larger sample to be compatible with studies based on small (∼100 stars) samples of solar twins, but we now extend them to both sub- and supersolar metallicities. The α-elements show differing behaviour: the hydrostatic α-elements O and Mg show a steady decline with time for all metallicities, while the explosive α-elements Si, Ca, and Ti are nearly constant during the thin-disc epoch (ages $\lesssim \! 12$ Gyr). The s-process elements Y and Ba show increasing [X/Fe] with time while the r-process element Eu has the opposite trend, thus favouring a primary production from sources with a short time delay such as core-collapse supernovae over long-delay events such as neutron star mergers.